University jubilees and university history writing : a challenging relationship - Dhondt, Pieter, 1976- (History of science and medicine library. Scientific and learned cultures and their institutions ;, 2015)
Through various case studies, this book shows the continuity of the close relationship between jubilees and university historiography and the impact of this interaction on the jubilee publications and academic heritage. Yet it also goes beyond the jubilee by presenting three other ways of writing university history.